Advance care planning in multiple sclerosis (ConCure-SM): A multicenter single-arm pilot and feasibility study - Alessandra Solari; Ludovica De Panfilis; Roberta Martina Zagarella; Luca Ghirotto; Mariangela Farinotti; Alberto Gajofatto; Maria Grazia Grasso; Paola Kruger; Alessandra Lugaresi; Katia Mattarozzi; Sara Montepietra; Francesco Patti; et al. (PLoS ONE, 2025)
Background Advance care planning (ACP) practice in people with progressive multiple sclerosis (PwPMS) remains limited. ConCure-SM project aims to assess the effectiveness of a structured ACP intervention (clinician’s training programme and use of a booklet during ACP conversations) using a multi-phased design. Methods Single-arm pilot/feasibility trial involving PwPMS, their significant others (SOs), and clinicians from six Italian centers. Primary study outcome was completion of an advance care plan document (ACP-Doc). Other outcomes included safety, feasibility of enrollment and assessment, and (analyzed using mixed-methods approach) Hospital Anxiety and Depression Scale (HADS), quality of communication, quality of life (MSQOL-29), and caregiver burden. Participants were interviewed to identify factors influencing the ACP implementation process. Results Seventy-five PwPMS were eligible out of 164 screened; 56/75 (75%) refused participation and 19 were included. Of these, 11 (58% vs 30% hypothesized) completed the ACP-Doc. A total of 25 adverse events (increase in anxiety) occurred, three possibly related to the intervention, and we found a worsening of HADS-Anxiety score (p = 0.02) and MSQOL-29 mental health composite score (p = 0.04) during follow-up. PwPMS/SO interviews revealed four themes: significance of the ACP process (on the individual, on relation with clinicians), its impact (on emotions, on family relations), preparedness as key, and challenges (practicability, SO commitment). Barriers and facilitators for ACP were identified in two clinician focus groups. Conclusions The intervention supported neurologists in guiding PwPMS in their ACP. However, trial findings and the high proportion of refusals point to the need to enrich the intervention with a new component targeting PwPMS and SOs. Trial registration ISRCTN48527663.